TYPES OF ROOT AND AFFIXAL MORPHEMES - Iskandarov Hayotbek; Abdurakhmanova Zilola (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation A root morpheme, or simply a root, is the core form of a word to which affixes can be added. It's the foundational element that carries the principal meaning of a word. Roots are often morphemes that can stand alone as words in their own right. Affixal morphemes, also known as affixes, are morphemes attached to a root or stem to create a new word or modify the meaning of the existing word. They can be prefixes, suffixes, infixes, or circumfixes.